2019
DOI: 10.3390/ijms20153656
|View full text |Cite
|
Sign up to set email alerts
|

MAS NMR on a Red/Far-Red Photochromic Cyanobacteriochrome All2699 from Nostoc

Abstract: Unlike canonical phytochromes, the GAF domain of cyanobacteriochromes (CBCRs) can bind bilins autonomously and is sufficient for functional photocycles. Despite the astonishing spectral diversity of CBCRs, the GAF1 domain of the three-GAF-domain photoreceptor all2699 from the cyanobacterium Nostoc 7120 is the only CBCR-GAF known that converts from a red-absorbing (Pr) dark state to a far-red-absorbing (Pfr) photoproduct, analogous to the more conservative phytochromes. Here we report a solid-state NMR spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(94 citation statements)
references
References 71 publications
(143 reference statements)
7
86
1
Order By: Relevance
“…Thus, the observed spectral shift of P fr appears to be inducedb yi nteractions of the PCB chromophore with the "tongue" region of the g2 domain in g1g2. [32,34] Interestingly, we find that the quantum yield (QY) of the P r !P fr transition is increased from~8% to~13 %( as imilarQ Yi so bserved in the related Cph2 [35] ). Hence, it follows that while the presenceo f the g2 domain does not directly affect the spectralp roperties of the P r form it does affect its photochemistry.…”
Section: Photochromism Of All2699 G1 G2mentioning
confidence: 85%
See 4 more Smart Citations
“…Thus, the observed spectral shift of P fr appears to be inducedb yi nteractions of the PCB chromophore with the "tongue" region of the g2 domain in g1g2. [32,34] Interestingly, we find that the quantum yield (QY) of the P r !P fr transition is increased from~8% to~13 %( as imilarQ Yi so bserved in the related Cph2 [35] ). Hence, it follows that while the presenceo f the g2 domain does not directly affect the spectralp roperties of the P r form it does affect its photochemistry.…”
Section: Photochromism Of All2699 G1 G2mentioning
confidence: 85%
“…Recently,i tw as reported that in g1 and in g1g2 there exists ab road distribution of ground state subconformations that rapidly interconvert in solution. [32,48] These subconformations could partially contribute to the observed distributed character of the P r * decay kinetics. However,t heir rapid interconversion denotes that they are separated by low energetic barriers, and thus cannot explain the large exciteds tate barriert hat determines the relatively slow P r * decay kinetics (100 ps timescale).…”
Section: Distributed Character Of the P R * Photoisomerization Kineticsmentioning
confidence: 99%
See 3 more Smart Citations